Praktik Agoforestri Pada Areal Perhutanan Sosial Wanagiri Di Kabupaten Sumbawa:Dari Perspektif Ontologi: Agroforestry Practices in the Wanagiri Social Forestry Area in Sumbawa Regency: From an Ontological Perspective - Hartono, Yadi; Sarjan, Muhammad (JURNAL HUTAN TROPIKA, 2025)
Agroforestry as a sustainable land use system not only represents ecological practices but also reflects the worldview and values of local communities. This study aims to explore agroforestry practices in the Wanagiri social forestry area/HKm in Sumbawa Regency from an ontological perspective, by examining the community's view of the relationship between humans, plants, and the environment. Qualitative methods were used through participatory observation and in-depth interviews with farmers and traditional leaders. The results of the study indicate that agroforestry practices in the Wanagiri social forestry/HKm area in Sumbawa Regency are rooted in the local knowledge system of the Balinese community, which has been passed down from their region of origin. The Balinese ethnic group in the Wanagiri social forestry area/HKm are migrants from Karangasem who arrived in 1985 through a transmigration program. In managing the forest in the Wanagiri social forestry area/HKm, the Balinese community emphasizes harmony between humans and nature. The ontological perspective of the local community reflects a strong relationality, where trees and land are not merely seen as resources but as integral parts of social and spiritual life. This finding indicates the importance of considering ontological frameworks in the development of sustainable and contextual agroforestry policies.